Economisch belang van de Belgische havens: Vlaamse zeehavens, Luiks havencomplex en haven van Brussel – Verslag 2006 - Saskia Vennix (National Bank of Belgium, 2008)
– This paper is an annual publication issued by the Microeconomic Analysis service of the National Bank of Belgium. The Flemish maritime ports (Antwerp, Ghent, Ostend, Zeebrugge), the Autonomous Port of Liège and the port of Brussels play a major role in their respective regional economies and in the Belgian economy, not only in terms of industrial activity but also as intermodal centres facilitating the commodity flow. This update paper1 provides an extensive overview of the economic importance and development of the Flemish maritime ports, the Liège port complex and the port of Brussels in the period 2001 - 2006, with an emphasis on 2006. The port of Brussels has been included in the analysis for the first time. Focusing on the three major variables of value added, employment and investment, the report also provides some information about the financial situation in each port except for Brussels. These observations are linked to a more general context, along with a few cargo statistics. Annual accounts data from the Central Balance Sheet Office were used for the calculation of direct effects, the study of financial ratios and the analysis of the social balance sheet. The indirect effects of the activities concerned were estimated in terms of value added and employment, on the basis of data from the National Accounts Institute. In terms of quantity of cargo handled, 2006 was an excellent year for the Flemish maritime ports as a whole, driven by the world trade expansion. Direct value added rose in all Flemish port, except for Antwerp. Direct employment also increased, mainly in the maritime branches as a result of seaborne traffic growth. Investment on the other hand, took a downward plunge after the exceptionally high amounts in 2005. This was mainly due to a number of shipping companies and - to a lesser extent - the completion of the Deurganckdok in Antwerp. The current changes in world trade patterns have a substantial impact on the activities in the Flemish ports. To cope with the accelerating internationalisation of port competition and the tremendous growth of containerised seaborne transport, the ports need to constantly adapt their infrastructures, through innovation and investment. As major logistic centres, they have to face the challenge of responding to increasing demand in terms of capacity, while adding as much value as possible to the goods passing through them. To face this challenge, they try to focus on particular branches or aspects for which they believe they hold all the winning cards. This has become absolutely vital in a climate of growing regional and international competition, accentuated by the booming Asian economies. All figures indicate that the situation is improving for the port of Liège. The growth of value added, investment and quantity of cargo handled exceeds last year's figures. Employment still decreases but to a lesser extent. Moreover, the future is looking even brighter as the TriLogiPort project should begin to make progress, the blast furnace 6 of Arcelor in Seraing has been reopened, a new bioethanol plant is being built in Wanze and several works developing the infrastructure are being carried out. The last few years, the quantity of cargo handled at the port of Brussels has stabilised. In terms of land available for port related activities, the port of Brussels has reached its limits. As a result, the extension of the infrastructure is one of the main priorities, all the more because the port authority has set ambitious goals for the near future. The present report provides a comprehensive account of these issues, giving details per economic sector, though the comments are confined to the main changes that occurred in 2006.
Keywords: C67; H57; J21; L22; L91; L92; R15; R34; R41; 330; branch survey; maritime cluster; subcontracting; indirect effects; transport intermodality; public investments.